Overview of Governance and Rampant Corruption in Land Administration in Bangladesh - Chowdory , Mohammad Moin Uddin (South Asian Journal of Social Sciences and Humanities, 2024)
This study focuses on the governance and corruption in the land management system of Bangladesh and the effect of these factors on the tenure security of land and the country’s economic growth. This study used a quantitative research design. The research outcomes show that corruption is systematic in all levels of land management, thus eroding the security of tenure, and worsening social inequalities. The new governance reforms have also been implemented to curb corruption; however, these changes’ impact has been rather poor. In light of the findings of the study, there is a well-established need for systematic reform to improve the situation in Bangladesh through digitization of land records, better transparency, and higher accountability in the land administration sector. The investigation presented in this research adds to the discussion of governance and development and offers practical policy suggestions that relate to fighting corruption and enhancing the efficient utilization of Bangladeshi land.